ISOLATION AND SCREENING OF ANTI-MICROBIAL COMPOUNDS PRODUCED BY FLUORESCENT PSEUDOMONADS AGAINST PV. XANTHOMONAS AXONOPODIS PUNICAE (Journal of Plant Disease Sciences, 2023)
Xanthomonas axonopodis pv. punicae is the most prevalent pathogen in majority of the pomegranate cultivating areas of India which causes bacterial blight. There is a need to develop ecologically friendly methods to prevent pomegranate production loss caused by this disease. The present study aimed to identify the most efficient native strains of antagonistic fluorescent pseudomonads against X. axonopodis pv. punicae, as well as the anti-microbial compounds produced by such efficient strains. Out of 99 colonies of fluorescent pseudomonads collected from different rhizosphere soils of pomegranate, the dual culture assay against X. axonopodis pv. punicae revealed that 83 colonies showed inhibitory effect while nine strains were found highly potent antagonists. In the present study, the bio-assay of crude cell free extracts of nine efficient strains, only five strains showed inhibition ofX. axonopodis pv. punicae culture. The crude cell free extract of these five strains were separated on a TLC plate which yielded four to six metabolites with different Rf values ranged from 0.23 to 0.86. Eluted portion of all the metabolites failed to show the inhibition activity exceptonly one metabolite produced by FP-64 with Rf value of 0.67 whichshowed an inhibition of 1.50 cmin diameter.
Keywords: Anti-microbial compounds; Bacterial blight; Fluorescent; Pseudomonads